A 1.4 Year Old Child Language Acquisition (Case Study on a Bilingual Family) - Noermanzah Noermanzah (PAROLE: Journal of Linguistics and Education, 2015)
This paper presents the phonological and morphological aspects of language acquisition of the child aged 1.4 years of a bilingual family. The researcher used a qualitative approach by using case study method. Data collection technique used is documentation and observation. Data were analyzed using inductive models, with the steps: observation of data, insights into the structure of the data, the formulation of hypotheses, testing hypotheses. The results of this research indicate that the language acquisition of children aged 1.4 years on average amounted to 40 words that structure largely intact as a word yet, but it is understood its meaning. Language acquisition obtained from the two languages simultaneously (simultaneous bilingual) language is Indonesian and Bengkulu. The children are able to pronounce vowels a, i, u, e, and o in forming words. Then, the boy also has been able to say 13 consonants, namely b, c, d, h, j, k, m, n, p, s, t, w and y.                                Tujuan penelitian ini adalah untuk menjelaskan aspek fonologis dan morfologis pemerolehan bahasa anak berusia 1,4 tahun dalam keluarga bilingual. Penelitian adalah studi kasus menggunakan pendekatan kualitatif. Pengumpulan data dengan metode dokumentasi dan observasi. Data dianalisis dengan model induktif dengan beberapa langkah, yaitu pengamatan terhadap objek yang diteliti, pemahaman terhadap struktur data, penyusunan hipotesis, dan pengujian hipotesis. Hasil penelitian ini menunjukkan bahwa pemerolehan bahasa anak 1,4 tahun rata-rata memiliki 40 kata dengan memahami maknanya. Pemerolehan bahasa yang dilakukan dapat dikategorikan sebagai dwibahasawan simultan, yaitu Indonesia dan Bengkulu. Anak itu mampu menghasilkan bunyi vokal a, i, u, e, dan o dalam membentuk kata. Selain itu, anak tersebut dapat menghasilkan 13 konsonan, yaitu b, c, d, h, j, k, m, n, p, s, t, w dan y.